Mechanics of Total Ankle Replacement During Flexion in Relation to Geometrical Design: a Finite Element Study - Ajmal Mohd Taqayuddin, Muhammad; Afzan Mohd Anuar, Mohd; Shuib, Solehuddin; Mohamed, Zulkifli; P.P. Abdul Majed, Anwar (International Journal of Engineering and Technology, 2018)
Total ankle replacement (TAR) procedure is carried out to reduce the pain due to arthritis and trauma in patients. The Â failure of TAR implants occurs through various wear mechanisms in the polyethylene due to high ankle load, leads to instability as well as loosening problem. The objective of this project is to assess the performance of Salto Talaris (TAR) implants before and after design modification. In the present study, the computational model of Salto Talaris and the modified design was developed using CATIA V5R20 while the finite element analysis (FEA) was performed in ANSYS V18. The results have shown that the maximum von Mises stress induced in the polyethylene insert for Salto Talaris and the new design were 13.9 MPa and 8.7 MPa, respectively, with applied 880 N of axial ankle load. The modified version exhibited better performance due to elimination of edge loading with good contact area. Design modification is essential to lower the stress induced at PE insert, hence reduce the failure of TAR prosthesis.Â Â